Exploring New Strategies for Ultrahigh Strength Steel via Tailoring the Precipitates - Tian, Jialong; Jiang, Zhouhua (Frontiers in Materials, 2021)
Ultrahigh strength (UHS) steels have shown great potential in the field of high-end equipment manufacturing in demand of lightweight engineering and performance upgrade. A significant research effort has been directed toward the development of advanced UHS steels with excellent combination of strength and toughness. In the course of development, tailoring precipitates by means of composition design and process optimization is absolutely a critical module. In this mini review, typical UHS steels strengthened by carbides and intermetallics are systematically summarized and discussed. With the increase of strength, the toughness losses of UHS steels strengthened by carbides and intermetallics have been compared in detail. In particular, the in-depth mechanisms leading to various strength/toughness variation trends have been discussed, extracting the bottleneck in developing new generation UHS steels containing merely one type precipitate. Meanwhile, prospects on designing advanced UHS steels strengthened by coexisting dispersive precipitates have been proposed to achieve better performances.